Mineralogenic characteristics of osteogenic lineage-committed human dental pulp stem cells following their exposure to a discoloration-free calcium aluminosilicate cement. Issue 10 (October 2016) - Niu, Li-na; Pei, Dan-dan; Morris, Matthew; Jiao, Kai; Huang, Xue-qing; Primus, Carolyn M.; Susin, Lisiane F.; Bergeron, Brian E.; Pashley, David H.; Tay, Franklin R.
Graphical abstract: Highlights: Osteogenic differentiation of hDPSCs was enhanced after exposed to White MTA or Quick-Set2. White MTA displayed better mineralogenic stimulation capacity than Quick-Set2 on hDPSCs. Intracellular mineral-containing vesicles were found in differentiated hDPSCs. Abstract: Objectives: An experimental discoloration-free calcium aluminosilicate cement has been developed with the intention of maximizing the beneficial attributes of tricalcium silicate cements and calcium aluminate cements. The present study examined the effects of this experimental cement (Quick-Set2) on the mineralogenic characteristics of osteogenic lineage-committed human dental pulp stem cells (hDPSCs), by comparing the cellular responses with a commercially available tricalcium silicate cement (white mineral trioxide aggregate (ProRoot ® MTA); WMTA). Methods: The osteogenic potential of hDPSCs exposed to the cements was examined using qRT-PCR for osteogenic gene expressions, Western blot for osteogenic-related protein expressions, alkaline phosphatase enzyme activity, Alizarin red S staining, Fourier transform infrared spectroscopy and transmission electron microscopy of extracellular calcium deposits. Results: Results of the six assays indicated that osteogenic differentiation of hDPSCs was significantly enhanced after exposure to the tricalcium silicate cement or the experimental calcium aluminosilicate cement, with the former demonstrating better mineralogenic stimulation capacity. Significance: The better osteogenic stimulating effect of the tricalcium silicate cement on hDPSCs may be due to its relatively higher silicate content, or higher OH − and Ca 2+ release. Further investigations with the use of in vivo animal models are required to validate the potential augmenting osteogenic effects of the experimental discoloration-free calcium aluminosilicate cement.